New mouthless nematode of the genus Parastomonema Kito, 1989 (Nematoda: Siphonolaimidae) from a mangrove forest on the coast of Thailand, and erection of the new subfamily Astomonematinae within the Siphonolaimidae - Kito, Kenji; Aryuthaka, Chittima (Zootaxa, 2006)
A new species of mouthless nematode Parastomonema papillosum sp. nov. was described based on specimens collected in muddy sediments of a mangrove forest in Samut Songkhram, Thailand. Parastomonema papillosum sp. nov. is the second species of the genus and differs from the type species P. fijiense Kito, 1989 in having short body length (1.5–3.0 mm), short cephalic setae (1.5–2.6 µm), and a weakly cuticularized gubernacular apophysis in the male. Astomonematinae subfam. nov. was erected for the two mouthless genera Astomonema and Parastomonema in the Siphonolaimidae based on the diagnostic feature of a degenerate alimentary canal and female reproductive system with paired ovaries.